Diversity of Meliaceae family in Bogani Nani Wartabone national park (Hungayono tourism object) - Bantali, Moh Sapitri; Baderan, Dewi Wahyuni K.; Angio, Melisnawati H (Bioculture Journal, 2025)
Introduction: The Meliaceae family is a group of flowering plants that are widely distributed in tropical and subtropical regions around the world. Some of its members have important economic value. Based on initial surveys in the Bogani Nani Wartabone National Park area, especially the Hungayono tourist attraction area of Gorontalo Province, it is known that there are various species of Meliaceae familli plants. However, it has not been identified what types of Meliaceae plants are and how the value of diversity index in the tourist attraction area. Methods: The purpose of this study was to determine how the diversity of Meliaceae plant species in the Hungayono tourist attraction area of Gorontalo Province. Data collection techniques using exploratory or cruising methods using sampling techniques Probability Sample. Findings: The results of the study found 10 species of Meliaceae familli plants in the Hungayono tourist attraction area. The index value of plant diversity of Meliaceae familli found in the Hungayono tourist attraction area is 1.91 with moderate criteria which indicates a fairly stable ecosystem condition. Conclusion: these findings provide valuable baseline data on the Meliaceae family in the region, contributing to future conservation and biodiversity management efforts in the area. Novelty/Originality of this article: The novelty of this research lies in the first recorded identification and diversity assessment of Meliaceae species in the Hungayono tourist attraction area.